Spray-Drying Hen Eggs: Effects of the Egg Yolk to Egg White Ratio and Sucrose Addition on the Physicochemical, Functional, and Nutritional Properties of Dried Products and on Their Amino Acid Profiles - Liliana M. Vargas-del-Río; Alexis García-Figueroa; Alejandro Fernández-Quintero; Aida Rodríguez-Stouvenel (Applied Sciences, 2022)
Manufactured egg powders can be formulated to produce food products that vary in their properties. The present study aims to determine the effect of egg white content on the physicochemical characteristics and on the functionality and nutritional value of dried whole egg (WE), egg white (W), and an egg yolk/white mixture in a 1:3 ratio (M1:3). These fresh egg products were spray-dried using sucrose—an agent recognized for its effect of protecting the protein in the egg during the drying process. Experiments were conducted in a laboratory-scale spray dryer, operated under controlled conditions, with an air inlet temperature of 120 °C. In the dried products, water activity, water solubility index, color, and pH were affected significantly as a function of the fresh egg component ratio and the added sucrose. The wettability and dispersibility in water of egg powder were improved when sucrose was added to the WE. The water-holding capacity was highest in dried egg white, and higher in the M1:3 mixture without sucrose added than in the WE with 5% sucrose. The results suggest that modifying the ratio of fresh egg yolk to egg white could lend some control over the protein and fat contents of dried egg products and over their functional properties.